2011
DOI: 10.5137/1019-5149.jtn.4050-10.2
|View full text |Cite
|
Sign up to set email alerts
|

Dural metastases in chronic myeloid leukemia presenting as subdural hematoma”

Abstract: Subdural hematoma (SDH) has been reported in 0.5-4% of all intracranial metastatic tumors. Chronic SDH has been reported in intracranial metastases from both solid and haematological malignancies. Here we report recurrent SDH in a patient with chronic myeloid leukaemia (CML) following dural metastases. An elderly male patient a known case of CML was admitted to our casualty with symptoms of headache and altered sensorium and imaging revealed a large right fronto temporo parietal chronic SDH. This was surgicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“… 12 17) Also, many case reports showed a relationship between brain metastasis of malignant neoplasm and CSDH. 1 8 10 16) Authors suggested a multifactorial pathogenesis of CSDH in malignancy such as dural vessel occlusion and rupture by tumor cells, tumor necrosis and chemotherapy-induced thrombocytopenia or disseminated intravascular coagulation secondary to an underlying malignancy. 11) Authors suggested that CSDH seems easily to occur in patients with malignant neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“… 12 17) Also, many case reports showed a relationship between brain metastasis of malignant neoplasm and CSDH. 1 8 10 16) Authors suggested a multifactorial pathogenesis of CSDH in malignancy such as dural vessel occlusion and rupture by tumor cells, tumor necrosis and chemotherapy-induced thrombocytopenia or disseminated intravascular coagulation secondary to an underlying malignancy. 11) Authors suggested that CSDH seems easily to occur in patients with malignant neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of bleeding usually indicate disease progression in the case of the progression of qualitative or quantitative thrombocytic abnormalities. [1,10] In a few cases, bleeding in CML in CP after diagnosis can be caused by metastasis of leukemic cells, [7] interferon-γ (IFN-γ) induced inhibitor of clotting factors [16] or tyrosine kinase inhibitor (TKI) agents triggered platelet dysfunction. [17]…”
Section: Discussionmentioning
confidence: 99%
“…[1] The occurrence of bleeding in CML usually suggests disease progression, which is caused by abnormal quantity or quality of thrombocyte. [1] Though anecdotal, the reported CML in CP initially presenting with hematoma includes intramuscular hematoma, [2,3] mediastinal hematoma, and hemothroax, [4] spinal epidural hematoma, [5] cerebellar hemorrhage, [6] subdural hematoma, [79] and deep soft-tissue hematomas. [10] Except for blast cell infiltration, [7] acquired von Willebrand factor (VWF) deficiency [8] or speculated platelet dysfunction [10] associated with hyper-thrombocytosis, most reported cases show almost normal results of clotting screening tests, including PT, activated partial thromboplastin time (APTT), thromboplastin time (TT), and platelet counting.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter cases, contrary to the findings of the present case, immature blasts were the predominant cells in the patients' cerebrospinal fluid. Dural metastasis of CML is rare, but it has been reported ( 14 , 15 ), and leukemic infiltration of the dura mater is considered to be a cause of chronic subdural hematoma ( 15 ). Hypertrophic panmeningitis is a rare disorder characterized by fibrosis and thickening of the dura matter, and it can occur idiopathically or secondary to an infection, autoimmune disorder, or malignancy, including CML ( 16 ).…”
Section: Discussionmentioning
confidence: 99%